Darah Sebagai Pengingat: Kajian Filosofis Tentang Kesadaran Genetik dan Relasi Leluhur di Budaya Timor - Bernabas Unab; Yogina Maria Saapan (Perspektif, 2026)
This article arises from a reflection on Timorese culture, which perceives blood as a symbol of connection with ancestors through rituals of remembrance. The purpose of this study is to reinterpret the meaning of blood not merely as a biological or ritual element but as an existential reminder affirming the continuous relational bond between the living and their ancestors. Using a relational philosophical approach (Levinas, Marcel) and incarnational theology, this analysis employs literature review and symbolic interpretation. The results reveal a new ethical dimension; the relationship with ancestors does not rely on ritual performance but on genetic awareness embodied in the descendants. In conclusion, blood becomes a symbol of relational consciousness that transcends biological and spiritual boundaries, affirming the human responsibility to live out ancestral values as the truest form of remembrance and respect